Human development and the explosion of democracy: Variations of regime change across 60 societies - Christian Welzel; Ronald Inglehart (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
Recently scholars identified a global explosion of democracy as a sharply distinctive period within Huntington's Third Wave of democratization. So far the role of modernization has not been analyzed with particular regard to this outstanding phase of democratization. Given that modernization has economic as well as cultural aspects, we test two prominent theses. First, we test Przeworski/Limongi's claim that transitions to democracy do not derive from economic modernization. Using a graded measure of regime change, we present evidence to the contrary. Second, we test Inglehart's finding that modern mass attitudes play a negligable role in promoting regime change to democracy. To the contrary again, we show that one aspect of cultural modernization, mass-level liberty aspirations, has a positive impact on democratic change' even stronger than economic modernization. Third, we unfold the concept of Human Development to establish a more general argument on the causal mechanism in the modernization- democratization nexus. Our data cover 60 societies of the World Values Surveys, representing nearly 50 per cent of all regime changes in the world since 1972. – – Jüngere Forschungsarbeiten haben eine globale Explosion der Demokratie identifiziert, die eine scharf eingegrenzte Periode innerhalb Huntingtons breiterer Definition der Dritten Demokratisierungswelle bildet. Mit Blick auf diese hervorstechende Demokratisierungsphase ist die Rolle von Modernisierungsfaktoren bisher noch nicht untersucht worden. Ausgehend davon, dass Modernisierung ökonomische und kulturelle Aspekte hat, prüfen wir zwei prominente Thesen. Zunächst testen wir Przeworski/Limongis Behauptung, dass Regimewechsel zur Demokratie nicht von ökonomischer Modernisierung befördert werden. Unter Verwendung eines kontinuierlichen Maßes für Regimewechsel kommen wir zu einem gegenteiligen Ergebnis. Zum zweiten testen wir Ingleharts Befund, dass moderne Einstellungen der Bürger ebenfalls keine positive Wirkung auf Regimewechsel zur Demokratie hätten. Im Gegensatz auch zu diesem Befund kommen wir zu dem Ergebnis, dass ein wesentlicher Aspekt kultureller Modernisierung, nämlich die Verbreitung von Freiheitsansprüchen, sehr wohl einen positiven Effekt auf Regimewechsel zur Demokratie hat - mehr noch sogar als ökonomische Modernisierung. Zum dritten entfalten wir das Konzept der Humanentwicklung, um ein generelleres Verständnis der Wirkungszusammenhänge im Modernisierungs-Demokratisierungs- Nexus zu etablieren. Unsere Daten decken 60 Gesellschaften aus den Weltwertestudien ab, auf die fast 50 Prozent aller Regimewechsel entfallen, die seit 1972 weltweit aufgetreten sind.
Keywords: 300